2020
DOI: 10.32473/edis-uw121-2020
|View full text |Cite
|
Sign up to set email alerts
|

White-tailed Deer of Florida

Abstract: The white-tailed deer (Odocoileus virginianus) is the most economically important big game mammal in North America and Florida. This 12-page fact sheet written by Raoul K. Boughton, Bethany Wight, Samantha Wisely, Karen Hood, and Martin B. Main and published by the UF/IFAS Department of Wildlife Ecology and Conservation provides an overview of the various subspecies of white-tailed deer with populations in Florida and describes their history, biology, and manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For instance, the relative frequency of the "glacier" bear (Ursus americanus ) is 0.4% against 96.6% of black bears (Lewis et al, 2020). Four different coat colour morphs in sea lion (Arctocephalus gazella ) on Livingston Island, Antarctica, occurred at a frequency of only 0.02-0.04% (Acevedo, Torres, & Aguayo-Lobo, 2009), and the "piebald" white-tailed deer in Florida, United States, occurred at a frequency of less than 1% (Boughton et al, 2020). Rare wild cat variants such as the golden tiger, white lion, and king cheetah have only been recorded a handful of times in history (Bottriell, 1987;Robinson & Vos, 1982;Zebley, Olson, & Ito, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the relative frequency of the "glacier" bear (Ursus americanus ) is 0.4% against 96.6% of black bears (Lewis et al, 2020). Four different coat colour morphs in sea lion (Arctocephalus gazella ) on Livingston Island, Antarctica, occurred at a frequency of only 0.02-0.04% (Acevedo, Torres, & Aguayo-Lobo, 2009), and the "piebald" white-tailed deer in Florida, United States, occurred at a frequency of less than 1% (Boughton et al, 2020). Rare wild cat variants such as the golden tiger, white lion, and king cheetah have only been recorded a handful of times in history (Bottriell, 1987;Robinson & Vos, 1982;Zebley, Olson, & Ito, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the relative frequency of the ‘glacier’ bear ( Ursus americanus ) is 0.4% against 96.6% of black bears within southeast Alaska (Lewis et al, 2020 ). Four different coat colour morphs in sea lion ( Arctocephalus gazella ) on Livingston Island, Antarctica, occurred at a frequency of only 0.02–0.04% (Acevedo et al, 2009 ), and the ‘piebald’ white‐tailed deer in Florida, the United States, occurred at a frequency of <1% (Boughton et al, 2020 ). Rare wild cat variants such as the golden tiger, white lion and king cheetah have only been recorded a handful of times in history (Bottriell, 1987 ; Robinson & De Vos, 1982 ; Zebley et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested prolonged high water caused by episodic tropical storms can result in elevated deer mortality rates (Fleming et al, 1994;Labisky et al, 1995Labisky et al, , 1999Loveless, 1959;MacDonald-Beyers & Labisky, 2005). Effect of water depth on deer survival can be mediated by shifts in space use toward lower quality forage areas (MacDonald-Beyers & Labisky, 2005), and increases in predation susceptibility related to decreased mobility and higher concentration of deer population in high water level conditions (Boughton et al, 2020). Previous studies suggested water depths exceeding 0.5 m are detrimental to deer populations (Labisky et al, 1999;Loveless, 1959;MacDonald-Beyers & Labisky, 2005).…”
Section: (B)mentioning
confidence: 99%